Law and Finance : Why Does Legal Origin Matter? - Beck, Thorsten; Demirguc-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2014)
A growing body of work suggests that cross-country differences in legal origin help explain differences in financial development. The authors assess two theories of why legal origin influences financial development. First, the "political" channel stresses that (1) legal traditions differ in the priority they give to the rights of individual investors compared with the state, and that (2) this has repercussions for the development of property rights and financial markets. Second, the "adaptability" channel holds that (1) legal traditions differ in their ability to adjust to changing commercial circumstances, and (2) legal systems that adapt quickly to minimize the gap between the contracting needs of the economy and the legal system's capabilities will foster financial development more effectively than would more rigid legal traditions. The authors use historical comparisons and cross-country regressions to assess the validity of these two channels.